Asteroid Companions in the Visible: WFPC 2 Images - A. D. Storrs; F. Vilas (The Planetary Science Journal)
We report the observation of six asteroidal companions in direct images of five asteroids from Hubble Space Telescope (HST). These are (45) Eugenia, (87) Sylvia, (93) Minerva, (107) Camilla (the discovery observation for this companion), and (121) Hermione. Images of the companions are barely above the threshold detectability and appear to have the same colors as the primary body. The primary asteroids are all resolved in the HST images, and their shapes and sizes can be clearly seen after reconstruction. These asteroids generally appear to be darker than expected from data in the literature, which is generally derived from ground-based adaptive optics observations and from IR radiometry (the SIMPS). The asteroids average about 5% smaller than their radiometric diameters, which is an effect of the image reconstruction process used here.